Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1242/jcs.02966
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell proliferation by the antizyme inhibitor: evidence for an antizyme-independent mechanism

Abstract: The antizyme inhibitor was discovered as a protein that binds to the regulatory protein antizyme and inhibits the ability of antizyme to interact with the enzyme ornithine decarboxylase (ODC). Blocking antizyme activity subsequently leads to increased intracellular levels of ODC and increased ODC enzymatic activity. We now report that antizyme inhibitor is a positive modulator of cell growth. Overexpression of antizyme inhibitor in NIH-3T3 mouse fibroblasts or in AT2.1 Dunning rat prostate carcinoma cells resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Downregulation of antizyme inhibitor activity is associated with reduced cell proliferation (Choi et al, 2005;Kim et al, 2006). Moreover, overexpression of AZI increases cell proliferation and promotes cell transformation (Keren-Paz et al, 2006;Kim et al, 2006) and high levels of AZI have been observed in gastric tumors (Jung et al, 2000). Our results show that overexpression of AZI induces aberrant synthesis of daughter centrioles as reported previously for the papillomavirus-16 E7 oncoprotein (Guarguaglini et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Downregulation of antizyme inhibitor activity is associated with reduced cell proliferation (Choi et al, 2005;Kim et al, 2006). Moreover, overexpression of AZI increases cell proliferation and promotes cell transformation (Keren-Paz et al, 2006;Kim et al, 2006) and high levels of AZI have been observed in gastric tumors (Jung et al, 2000). Our results show that overexpression of AZI induces aberrant synthesis of daughter centrioles as reported previously for the papillomavirus-16 E7 oncoprotein (Guarguaglini et al, 2005).…”
Section: Discussionsupporting
confidence: 83%
“…To address the possibility that regulation of ODC levels and activity may contribute to the centrosome-related activities of antizyme 1/AZI, we also investigated whether inhibition of ODC activity through the specific and irreversible ODC inhibitor difluoromethylornithine (DFMO) may affect centrosome homeostasis. At a DFMO concentration that has been shown to reduce ODC activity without substantial cytostatic activity (Kim et al, 2006), ODC inhibition did not affect centrosome abnormalities (data not shown). This indicates that inhibition of polyamine biosynthesis may not be the principal mechanism by which antizyme 1 and AZI regulate centrosome homeostasis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The sequence of the AZI siRNA was AAGAUCGUGAAGAAGCACAGU, which has been shown to be effective against AZI expression (31). To perform siRNA knockdown, ϳ2 ϫ 10 6 alveolar macrophages were placed in a well of a 6-well plate containing 2 ml of serum-free DMEM.…”
Section: Methodsmentioning
confidence: 99%